Structure-based virtual screening identifies dicoumarol as a potent InhA inhibitor against Nocardia seriolae infection in largemouth bass (Micropterus salmoides) - Jin-Lai Gu; Chen-Wang Lu; Lin-Feng Kuang; Jie He; Zheng-Ran Jian; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Zheng-Yang Zhou; Ming-Zhu Liu; Peng-Fei Li; Er-Long Wang; et al. (Aquaculture, 2027)

Generation of transgenic pigs with targeted insertion of a wildtype copy of human PKD2 gene - Xue-Lin Zhang; Jia-Ning Luo; Yue Cao; Jiu-Xiao Zhao; Yuan Zhang; Sai-Fei Xu; Le-Nan Zhuang; Jin He (Molecular Biology Reports, 2026)

Microscopic analysis of thermo-mechanical coupled effects on wellbore stability using a hybrid DEM-FDM approach - Dehao Meng; Fei Wang; Heinz Konietzky; Benguo He; Lin Chen (Computers and Geotechnics, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Numerical investigation with viscosity of nonlinear wave forces on a dual-tube submerged floating tunnel - Hong-fei Mao; Kai-lin Chen; Long Han; Zhong-bing Zhou; Yan-li He; Li-min Wang; Jing Xie (Ocean Engineering, 2026)

Microcystin-LR disrupts gut metabolic homeostasis through microbiota–metabolite axis remodeling in grass carp - Lixin Ma; Junyuan Tan; Xiaomin Zheng; Zhuojin He; Zhendong Qin; Li Lin; Fei Shi (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Structure-based classification for differential tyrosine kinase inhibitors efficacy of EGFR exon 19 deletions in non-small cell lung cancer - Wei Zhuang; Hua Bai; Jie Zhao; Weihua Li; Jiaojiao Yu; Zhijie Wang; Jianchun Duan; Xuezhi Hao; Yan Wang; Yutao Liu; Lin Wang; Lin Lin; et al. (Science China Life Sciences, 2026)

Numerical examination of hydrodynamic forces on a submerged forced rotating circular cylinder under wave action - Hong-Fei Mao; Long Han; Kai-Lin Chen; Jin-Bo Lin; Zheng-Lin Tian; Zhong-Bing Zhou; Hui Yang; Dong-Bin He; Li-Min Wang (Ocean Engineering, 2026)

Compositional profiling and inter-cultivar variation of flavonoids in some red table grapes cultivated in China: Assessing the quality-indicative potential of anthocyanins, flavonols, and flavanols - Shang-Lin Wang; Hai-Bei Yan; Lin Wang; Xing-Chi Chen; Jun Wang; Fei He (Food Chemistry, 2026)

Single-cell sequencing reveals metabolic reprogramming and immune regulation underlie the maintenance of teleost granulomas - Zheng-Yang Zhou; Zheng-Ran Jian; Jin-Lai Gu; Xin-Yuan Jiang; Jie He; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Chen-Wang Lu; Lin-Feng Kuang; Ming-Zhu Liu; Peng-Fei Li; et al. (Fish & Shellfish Immunology, 2026)

Microcystis aeruginosa-driven acute toxicity compromises immune–metabolic regulation and hepatocyte integrity in grass carp - Lixin Ma; Junyuan Tan; Xiaomin Zheng; Zhuojin He; Zhendong Qin; Li Lin; Fei Shi (Environmental Pollution, 2026)

Targeting perivascular adipose tissue in vascular aging: innovative translational strategies for disease prevention and monitoring - Peng-Xin Wang; Sha-Qi He; Bei Huang; Zi-Fei Liu; Feng Xu; Jun-Jie Yang; Sai Lu; Hui-Xiang Chen; Ze-Qiang Cai; Ling-Qing Yuan; Xiao Lin (Apoptosis, 2026)

Genetic regulation of insulin resistance surrogate index (TyG) and susceptibility to common diseases based on phenome-wide association study - Jia-Xin Wu; Ling-Huan Bu; Pei He; Ming-Hui Xia; Lin Bo; Fei-Yan Deng; Shu-Feng Lei (Molecular and Cellular Biochemistry, 2026)

Pasteurella multocida toxin induces apoptosis of respiratory epithelial cells by activating the PERK–NF-κB-DR5 signaling axis - Fei Wang; Yuhao Lei; Menghan Chen; Haixin Bi; Yayuan Luo; Fangfang Bai; Lin Hua; Huanchun Chen; Qigai He; Bin Wu; Zhong Peng (Veterinary Microbiology, 2026)

The effects of Polygonum capitatum in treating atopic dermatitis via modulation of the th2 cytokine pathway - Xiao-Gang Sun; Bin-He Yang; Xiao-Lin Yang; Fei Li; Li-Jun Hao (South African Journal of Botany, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Urban-suburban-rural gradient variations in mortality associated with compound exposure to heat wave and ozone pollution: A case-crossover study using small-area assessment - Kang Ma; Fengman Fang; Xiuya Xing; Yuesheng Lin; Cheng He; Youru Yao; Fei Tong; Jingli Zhu; Huadong Wang; Feiyan Zhang; Ruoxi Li (Journal of Environmental Management, 2026)

Time-variant deformation prediction and reliability assessment of slopes based on dynamic Bayesian model averaging - Chenbo Zhao; Chaoning Lin; Fei Wang; Huijun Qi; Ziwei Li; Tongchun Li; Yukun He (Engineering Geology, 2026)

Acute hepatic injury and metabolic response in hybrid grouper (Epinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂) to high-dose Vibrio harveyi infection - Zhuojin He; Xiaomin Zheng; Lixin Ma; Xing Lei; Zhilong Chen; Li Lin; Fei Shi (Veterinary Research Communications, 2026)

Manganese acts as savior rather than accomplice of antibiotic stress: Dual cycles of ROS scavenging and Mnammox - Dong-Jun Hou; Wei-Lin Guo; Qian-Ru Liu; Hong-Wei Yang; Qiu-You Xu; Yun-Fei He; Nian-Si Fan; Ren-Cun Jin (Journal of Water Process Engineering, 2026)

Autumnicola aciditolerans sp. nov., a novel member of the genus Autumnicola isolated from tidal flat in Zhoushan - Yang Li; Dong-Yan He; Jia-Wei Gao; Ke Cao; Yun-Fei Cao; Xing-Cheng Wang; Lin Xu; Yan Bai; Can Chen; Cong Sun (Antonie van Leeuwenhoek, 2026)

Oligochitosan‐Ameliorated Gut Microbiome and Metabolic Homeostasis in Hybrid Groupers ( Epinephelus lanceolatu ♂ × Epinephelus fuscoguttatus ♀) Infected With Vibrio harveyi - Fei Shi; Lixin Ma; Zhilong Chen; Zhuojin He; Xiaomin Zheng; Cuiyun Zou; Chun Liu; Li Lin (Journal of Fish Diseases, 2026)
Vibrio infections cause enteritis in grouper fish, leading to high mortality and stunted growth, which is a major challenge for aquaculture. Oligochitosans, marine prebiotics with bioactive properties, have proven their potential for growth promotion and immune regulation. However, the impacts of Vibrio harveyi on the gut microbiome of grouper fish and the potential of oligochitosans to modulate these effects remain poorly understood. This study investigates the influence of oligochitosan on the gut morphology, microbiota and metabolic patterns of hybrid grouper following low‐dose infection with V. harveyi . After 8 weeks of feeding, infected groupers exhibited histopathological changes in the intestine that were mitigated by oligochitosan, as evidenced by improved villus height and intestinal wall thickness. Microbiome sequencing revealed that oligochitosan enhanced α‐diversity and shifted bacterial communities, particularly increasing the abundance of Fusobacteriota and Actinobacteriota . Furthermore, the prevalence of Shewanella and Vibrio , which were more abundant in infected groupers, was reduced upon oligochitosan treatment. Metabolomic analysis indicated that lipid metabolism pathways were significantly altered in response to infection and oligochitosan intervention. Overall, oligochitosan modulates the gut microbiome and metabolite profiles, potentially protecting against V. harveyi ‐induced intestinal dysbiosis and metabolic disorders in hybrid groupers.

RSK2 facilitates beige fat formation through thermogenic and glycolytic pathways - Yan Cai; Jun-jun Chen; Lin-fei He; Yao Xu; Rui-qi Yang; Zhi-chun Yang (Journal of Thermal Biology, 2026)

A novel single-cell communication framework combining multi-omics reveals neuro-viral pathogenesis in fish - Yi-Fan Liu; Teng-Fei He; Zhi-Wen Zhao; Bao-Sheng Wu; Ying Liang; Lin-Miao Li; Jin-Ping Chen; Ye-Pin Yu (Marine Life Science & Technology, 2026)

Protective role of oligochitosan in intestinal homeostasis to Edwardsiella ictaluri in hybrid grouper (Epinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂) - Lixin Ma; Zhilong Chen; Zhuojin He; Xiaomin Zheng; Yutao Li; Cuiyun Zhou; Li Lin; Fei Shi (Aquaculture, 2026)

Numerical study on the influence of submerged breakwater slope on wave-current propagation behaviors - Hong-Fei Mao; Long Han; Kai-Lin Chen; Ying-Chao Ma; Jin-Bo Lin; Zheng-Lin Tian; Zhong-Bing Zhou; Ran Ji; Yan-Li He; Li-Min Wang (Ocean Engineering, 2026)

Soil nutrient heterogeneity induces foraging behavior but does not improve overall growth performance in six bamboo species - Lin-Xuan He; Li-Li Zheng; Jia-Yu Zhang; Xiao-Mei Zhang; Jing-Pin Lei; Mai-He Li; Fei-Hai Yu (Plant and Soil, 2026)

Influence of oligochitosan on hepatic immune-metabolic homeostasis in hybrid grouper infected with Vibrio harveyi - Lixin Ma; Zhilong Chen; Zhuojin He; Xiaomin Zheng; Jiawen Lin; Jiayue Yin; Cuiyun Zou; Li Lin; Fei Shi (Aquaculture International, 2026)

Mechanistic insights into electric field-assisted nanofiltration for efficient lithium-magnesium separation - Ao Wang; Dimitrios Toroz; Xiaofu Guo; Jie Liu; Shangming He; Liting Fei; Yingying Zhao; Shizhao Wang; Junsheng Yuan; Devis Di Tommaso; He Lin; Fei Li; et al. (Water Research, 2025)

Modulation of hepatic immune-metabolic pathways by oligochitosan in hybrid grouper infected with Edwardsiella ictaluri - Lixin Ma; Zhilong Chen; Zhuojin He; Xiaomin Zheng; Jiajia Li; Cuiyun Zou; Li Lin; Fei Shi (Fish & Shellfish Immunology, 2025)

Functional Analysis of the mstn1 Gene and Its Transcriptional Regulation by Mef2 Factors in Yellowfin Seabream, Acanthopagrus latus (Hottuyn, 1782) - Hong-Xi He; Ke-Cheng Zhu; Bao-Suo Liu; Hua-Yang Guo; Nan Zhang; Lin Xian; Teng-Fei Zhu; Dian-Chang Zhang; Min Yang (Fish Physiology and Biochemistry, 2025)

Association of compound exposure to heat wave and ozone pollution with cause-specific cardiopulmonary mortality: A space-time-stratified case-crossover study - Kang Ma; Fengman Fang; Yuesheng Lin; Fei Tong; Cheng He; Youru Yao; Jingli Zhu; Huadong Wang; Xiuya Xing; Feiyan Zhang; Ruoxi Li (Environmental Research, 2025)

Associations between per- and polyfluoroalkyl substances and type 2 diabetes: The modifying effects of lifestyle and genetic risk - Xu Cheng; Fei Wang; Jin Zhang; Yu Wang; Lu Liu; Lin Liu; Hong Guo; Junya Gao; Yafei Tan; Meian He (Journal of Hazardous Materials, 2025)

Separation and recovery of iron from vanadium extraction tailing slag by P204-P507 mixture collector flotation process - Yi-bo Wang; Jing-wei Li; Xiao-long Liu; Xin-fei Jiang; Yin-he Lin; Zhi Tian; Jun-jie Yin; Bing-qing Huang; Jia-xin Yang; Chen-xuan Wang; Zi-wang Wu; Shi-xing Ma; et al. (Journal of Environmental Chemical Engineering, 2025)

Spirulina-derived atomically dispersed Fe–N4 sites on g-C3N4 for efficient CO2 photoreduction - Haoxian Wang; Junjie Wang; Jin Xu; Jingkai Lin; Zhongshuai Zhu; Yazi Liu; Feihu Mu; Bin Huang; Fei Yu; Chenmin Xu; Shaogui Yang; Huan He; et al. (Chemical Engineering Journal, 2025)

Satellite-Based Emission Inversion for Air Pollutants and Greenhouse Gases: A Review - Zhe Jiang; Jintai Lin; Tai-Long He; Fei Jiang; Jianbing Jin; Kai Qin; Lu Shen; Panpan Yang; Zengliang Zang; Lin Zhang; Yuzhong Zhang; Bo Zheng; et al. (Journal of Meteorological Research, 2025)

Spatial heterogeneity in the joint effect of heat wave and ozone pollution on mortality at the township-level in China - Kang Ma; Fengman Fang; Yuesheng Lin; Fei Tong; Cheng He; Youru Yao; Jingli Zhu; Huadong Wang; Xiuya Xing (Sustainable Cities and Society, 2025)

Development and characterization of a high-resolution, high-sensitivity collinear resonance ionization spectroscopy system - Han-Rui Hu; Yang-Fan Guo; Xiao-Fei Yang; Zhou Yan; Wen-Cong Mei; Shao-Jie Chen; Yin-Shen Liu; Peng Zhang; Shi-Wei Bai; Dong-Yang Chen; Yong-Chao Liu; Shu-Jing Wang; et al. (Science Bulletin, 2025)

DEHP and its metabolite MEHP exposure impairs endometrial decidualization during early pregnancy via up-regulation of Mtmr6 - Li-Ping Tan; Liu Yuan; Yan Zhang; Jun-Lin He; Xin Yin; Yi-Dan Ma; Xue-Mei Chen; Wei-Ke Li; Fang-Fang Li; Ru-Fei Gao (Reproductive Toxicology, 2025)

CoFe-enhanced N-doped carbon nanotubes for activating peroxymonosulfate to remove carbamazepine under high-salinity conditions - Xiangxing Liang; Zhiyuan He; Jingxi Lin; Chuan Pu; Daixi Zhou; Fei Duan; Gang Lu; Mingshan Zhu (Journal of Water Process Engineering, 2025)

Aurantibrevibacter litoralis gen. nov. sp. nov. a Novel Member in the Family Flavobacteriaceae Isolated from Sediment of Tidal Flat Located in Ningbo, China - Yun-Fei Cao; Dong-Yan He; Yu-Ruo Wang; Ke Cao; Yang Li; Jia-Wei Gao; Xing-Cheng Wang; Lin Xu; Cong Sun; Xiao-Yun Yu (Current Microbiology, 2025)

A new illudane sesquiterpene from the edible fungus Pholiota nameko - Lian Yang; Huan Zhang; Shu-Hang He; Ju Xu; Xiao-Long Li; Fei-Xing Li; Dong-Mei Lin; Deng-Ji Lou; Xiao-Yan Yang (Natural Product Research, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Effect of cadmium-resistant Proteus mirabilis Ch8 on active ingredients and cadmium content of traditional Chinese medicine Ligusticum sinense cv. Chuanxiong - Ting Li; Lin Liu; Xiu-wen Bao; Fei-fei Liu; Xuan Zhang; Hao-ran Song; Si-jing Liu; Jing Bai; Qing-he Wang; Fei-lin Yang; Yang Li; Shu-qi Niu; et al. (Plant and Soil, 2025)

A new phenolic compound from Persicaria capitata - Lei He; Fei Zhong; Xing-Jun Chen; Ya-Ru Yang; Xue-Long Yan; Ming-Hui He; Xu Zhang; Mu-Zhen Wang; Yong-Qin Zeng; Qin-Feng Zhu; Zhu Zeng; Bo Tu; et al. (Natural Product Research, 2025)

Viscosity is a nonnegligible factor in the waste activated sludge fermentation: Taking hyaluronan as an example - Yan-Lin Hu; Kun Dai; Qing-Ting Wang; Chen-Yuan Zhou; Xing-Chen Huang; Xiao-Fei Yang; He-Liang Pang; Raymond Jianxiong Zeng; Fang Zhang (Water Research, 2025)

Bclaf1 mediates super-enhancer-driven activation of POLR2A to enhance chromatin accessibility in nitrosamine-induced esophageal carcinogenesis - Xiangjun Zhou; Xueqiong Zhou; Jun Li; Yingzheng He; Shizhen Qiu; Ye Xu; Zeyu Liu; Yina Yao; Jia Liu; Ying Wen; Sitong Xie; Jialong Chen; et al. (Journal of Hazardous Materials, 2025)

Tetrahedral framework nucleic acids loaded with chrysophanol for the treatment of chronic kidney disease - Xiaoshuai Gao; Dexuan Xiao; Wei Wang; Liao Peng; Fei Li; Yuchong He; Xin Wei; Yunfeng Lin (Chemical Engineering Journal, 2025)

Mechanistic insights into endometriosis: roles of Streptococcus agalactiae and L-carnitine in lesion development and angiogenesis - Yuan Zhuang; Ting Lyu; Yang Chen; Wei Li; Lei Tang; Shi-ping Xian; Peng-fei Yang; Lijie Wang; Qian-qian Zhang; Chaoming Mei; Yu-jing Lin; Zhixiang Yan; et al. (Angiogenesis, 2025)

Chloride corrosion destabilizes chelation of fresh and aged MSWI fly ash: Mechanism and long-term behavior - Jinyuan Lin; Lei Du; Deli Wu; Bo Yang; Xunchang Fei; Hongping He (Journal of Hazardous Materials, 2025)

Human Umbilical Cord Mesenchymal Stem Cells for the Treatment of Systemic Lupus Erythematosus via Glucose Metabolism of CD4+T Cells - Meng Ding; Lu Jin; Shaoxin Cui; Lin Yang; Jingjing He; Xiaoping Wang; Fei Chang; Qun Wang; Xue Liu; Hongtao Jin; Shuran Song; Min Shi; et al. (Stem Cell Reviews and Reports, 2025)

Removal and recovery of perchlorate from fireworks production wastewater through ion exchange and biological reduction processes - Jie Ma; Waseem ur Rahman; Peijun Du; Qimeng Li; Fei He; Guoyu Qiu; Guoxiang Wang; Xiaoguang Xu; Donglin Li; Ming Li; Shuizhong Lin (Journal of Environmental Management, 2025)

Pilot-scale demonstration of perchlorate-contaminated fireworks wastewater treatment through a combined ion-exchange and bioregeneration approach - Guoyu Qiu; Changkai Wang; Peijun Du; Qimeng Li; Fei He; Jie Ma; Donglin Li; Ming Li; Shuizhong Lin (Journal of Environmental Chemical Engineering, 2025)

Targeting ferroptosis for the treatment of female reproductive system disorders - Rui Ye; Yi-ming Mao; Yi-ran Fei; Yue Shang; Ting zhang; Zhe-zhong Zhang; Yong-lin Liu; Jun-yu Li; Shi-liang Chen; Yi-bo He (Journal of Molecular Medicine, 2025)

Decade-long application of preimplantation genetic testing for DMD/BMD: analysis of five clinical strategies and embryo recombination patterns - Weili Wang; Jing Dai; Xiao Hu; Wenbin He; Yifan Gu; Zhenxing Wan; Yi Zhang; Keli Luo; Wen Li; Qianjun Zhang; Fei Gong; Guangxiu Lu; et al. (Human Genetics, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Fucoxanthin ameliorates ulcerative colitis by maintaining the epithelial barrier via blocking JAK2/STAT3 signaling pathway - Jingjing Ma; Simei Yue; Yinghui Liu; Lingjiao Gong; Pengzhan He; Yingjie Yang; Zhengxin Fu; Danxiang Han; Qiang Hu; Fei Liao; Lin Xu (Toxicology and Applied Pharmacology, 2025)

Biotic plant-soil feedbacks alone do not explain why more diverse plant communities are less invasible - Hao-Ming Yuan; Xiao-Mei Zhang; Peter Alpert; Lin-Xuan He; Wei Xue; Lin Huang; Ling Peng; Fei-Hai Yu (Plant and Soil, 2025)

Role of C/EBP Homologous Protein in Vascular Stenosis After Carotid Artery Injury - Lin Teng; Qin Qin; Zi-yi Zhou; Fei Zhou; Cun-yu Cao; Chao He; Jia-wang Ding; Jian Yang (Biochemical Genetics, 2025)

Modeling and analysis of explicit dynamics of foot landing - Wu Ren; Ziya Zhao; Shuaiheng He; Xueling Zhang; Kailu Zhang; Yawei Li; Fei Lin; Zhenghui Wang; Guoan Zhao; Jinlong Chang; Qianfang Jia; Yi Yu; et al. (Medical & Biological Engineering & Computing, 2025)

Comprehensive analysis of epigenetic modifications in alfalfa under cadmium stress - Lin Chen; Xianyang Li; Hao Liu; Fei He; Mingna Li; Ruicai Long; Xue Wang; Junmei Kang; Qingchuan Yang (Journal of Hazardous Materials, 2025)

Cross-sectional and Longitudinal Associations Between Metal Mixtures and Serum C3, C4: Result from the Manganese‑exposed Workers Healthy Cohort - Sencai Lin; Junxiu He; Yinghua Zhou; Yu Bao; Xiuming Feng; Hong Cheng; Haiqing Cai; Sihan Hu; Lin Wang; Yuan Zheng; Mengdi Zhang; Qinghua Fan; et al. (Biological Trace Element Research, 2025)

A multi-omics approach reveals low temperature inhibition of flavones and flavonols accumulation in postharvest bananas via downregulation of MabHLH363 - Wen Song; Shu-Qin Lin; Qi Yin; Tian-He Liu; Lin-Zhi Gan; Jian-Ji Qi; Ying-Ying Yang; Wei Wei; Wei Shan; Jian-Fei Kuang; Jian-Ye Chen; Wang-Jin Lu (Postharvest Biology and Technology, 2024)

Numerical examination of wave forces on partially submerged horizontal circular cylinders near free surface - Hong-Fei Mao; Yuan-Ting Yang; Jin-Bo Lin; Zhong-Bing Zhou; Ming He (Ocean Engineering, 2024)

The role of Nocardia seriolae-induced autophagy in the development of chronic inflammation in the liver and the formation of granulomas in largemouth bass (Micropterus salmoides) - Shang-Jie Bai; Zheng-Ran Jian; Sheng-Yu He; Lin-Feng Kuang; Zheng-Yang Zhou; Chen-Wang Lu; Zhen-Dong Zhong; Jie He; Quan-Xin Xiong; Shuang-Yan Xiao; Peng-Fei Li; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Effects of soil microplastic heterogeneity on plant growth vary with species and microplastic types - Xiao-Mei Zhang; Wei-Long Li; Wei Xue; Michael Opoku Adomako; Min Tang; Lin-Xuan He; Fei-Hai Yu (Science of The Total Environment, 2024)

Corrigendum to “Lactiplantibacillus plantarum causes the abnormal fermentation of bacterial cellulose by Komagataeibacter nataicola during nata de coco production” [Food Bioscience 61 (October 2024) 104603] - Yaqian Yuan; Jiamu Kang; Shuangwen Fei; Xinling Qin; Xue Lin; Xiangrong Wang; Bo Zhao; Cuihua He; Sixin Liu; Congfa Li (Food Bioscience, 2024)

Lactiplantibacillus plantarum causes the abnormal fermentation of bacterial cellulose by Komagataeibacter nataicola during nata de coco production - Yaqian Yuan; Jiamu Kang; Shuangwen Fei; Xinling Qin; Xue Lin; Xiangrong Wang; Bo Zhao; Cuihua He; Sixin Liu; Congfa Li (Food Bioscience, 2024)

Evolution and disappearance of the paleo-West Pacific Anomaly: Implications to the future of South Atlantic Anomaly - Yaochen Yue; Jiawei Gao; Fei He; Yong Wei; Shuhui Cai; Huapei Wang; Yuqi Wang; Zhaojin Rong; Zhonghua Yao; Wei Lin; Yongxin Pan (Physics of the Earth and Planetary Interiors, 2024)

Mitochondrial damage and activation of NLRP3 induced by Yersinia ruckeri infection play an important role in the occurrence of diffuse acute inflammation of channel catfish (Ictalurus punctatus) - Chen-Wang Lu; Jie He; Quan-Xin Xiong; Zhen-Dong Zhong; Bin Yang; Sheng Lian; Meng-Meng Wang; Shang-Jie Bai; Lin-Feng Kuang; Zheng-Yang Zhou; Zheng-Ran Jian; Yuan-Chang Gao; et al. (Aquaculture, 2024)

Number of global change factors alters plant-soil feedbacks via its effect on soil fungal communities - Wei Xue; Lin Huang; James D. Bever; Cheng Du; Hao-Ming Yuan; Lin-Xuan He; Xiao-Mei Zhang; Fei-Hai Yu (Soil Biology and Biochemistry, 2024)

Revisiting the quantification of power plant CO2 emissions in the United States and China from satellite: A comparative study using three top-down approaches - Cheng He; Xiao Lu; Yuzhong Zhang; Zhu Liu; Fei Jiang; Youwen Sun; Meng Gao; Yiming Liu; Haipeng Lin; Jiani Yang; Xiaojuan Lin; Yurun Wang; et al. (Remote Sensing of Environment, 2024)

A new species of Populus and the extensive hybrid speciation arising from it on the Qinghai-Tibet Plateau - Yu-Jie Shi; Jia-Xuan Mi; Jin-Liang Huang; Fei-Fei Tian; Fang He; Yu Zhong; Han-Bo Yang; Fang Wang; Yu Xiao; Lin-Kai Yang; Fan Zhang; Liang-Hua Chen; et al. (Molecular Phylogenetics and Evolution, 2024)

Targeted Therapy of Spinal Cord Injury: Inhibition of Apoptosis Is a Promising Therapeutic Strategy - Wei He; Zhi-qiang Li; Hou-yun Gu; Qi-lin Pan; Fei-xiang Lin (Molecular Neurobiology, 2024)

Improved temperature prediction using deep residual networks in Hunan Province, China - Li Zhou; Fei Huo; Ronghui Cai; He Chen; Lin Xu (Meteorology and Atmospheric Physics, 2024)

Co-exposure of polystyrene nanoplastics and copper induces development toxicity and intestinal mitochondrial dysfunction in vivo and in vitro - Jinyu Rong; Chenwei Yuan; Xiang Yin; Xiaohan Wu; Fei He; Yixin Wang; Kelvin Sze-Yin Leung; Sijie Lin (Science of The Total Environment, 2024)

Molecular level toxicity effects of As(V) on Folsomia candida: Integrated transcriptomics and metabolomics analyses - Xianglong Lin; Weiran Wang; Fei He; Hong Hou; Fei Guo (Science of The Total Environment, 2024)

PM2.5 exposure-induced senescence-associated secretory phenotype in airway smooth muscle cells contributes to airway remodeling - Pei-Pei Cheng; Fan Yu; Shuai-Jun Chen; Xiao Feng; Zi-Heng Jia; Shi-He Hu; Xiao-Lin Cui; Ya-Ya Zhou; Qian Niu; Li-Mei Liang; Meng Wang; Lin-Jie Song; et al. (Environmental Pollution, 2024)

Microscopic insights into acid corrosion effects on chelated MSW incineration fly ash: Mechanisms of chelate destabilization - Jinyuan Lin; Xiaofeng Gao; Deli Wu; Bo Yang; Hongping He; Xunchang Fei (Journal of Cleaner Production, 2024)

Nocardia seriolae mediates granulomatous chronic inflammation of spleen in Micropterus salmoides through necroptosis - Zheng-Yang Zhou; Sheng-Yu He; Chen-Wang Lu; Shang-Jie Bai; Lin-Feng Kuang; Bin Yang; Sheng Lian; Zheng-Ran Jian; Meng-Meng Wang; Shuang-Yan Xiao; Qing Yu; Ming-Zhu Liu; et al. (Aquaculture, 2024)

A model of hybrid speciation process drawn from three new poplar species originating from distant hybridization between sections - Yu-Jie Shi; Jin-Liang Huang; Jia-Xuan Mi; Jing Li; Fan-Yu Meng; Yu Zhong; Fang He; Fei-Fei Tian; Fan Zhang; Liang-Hua Chen; Han-Bo Yang; Hong-Lin Hu; et al. (Molecular Phylogenetics and Evolution, 2024)

Instability in a carbon pool driven by multiple dissolved organic matter sources in a eutrophic lake basin: Potential factors for increased greenhouse gas emissions - Jie Ma; Muchun Zhou; Yu Peng; Ya Tuo; Chuanqiao Zhou; Kexin Liu; Yilin Huang; Fei He; Qiuying Lai; Zhihui Zhang; Tsuyoshi Kinouchi; Shuyin Li; et al. (Journal of Environmental Management, 2024)

A pleiotropic SIS-based hydrogel with immunomodulation via NLRP3 inflammasome inhibition for diabetic bone regeneration - Ning Sheng; Fei Xing; Qing-Yi Zhang; Jie Tan; Rong Nie; Kai Huang; He-Xi Li; Yan-Lin Jiang; Bo Tan; Zhou Xiang; Hui-Qi Xie (Chemical Engineering Journal, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Widespread clay authigenesis and highly congruent silicate weathering in the Marinoan aftermath - Yi-Sheng Yin; Guang-Yi Wei; Philip A.E. Pogge von Strandmann; Maxwell A. Lechte; Simon V. Hohl; Yi-Bo Lin; Da Li; Tianyu Chen; Tao Yang; Feifei Zhang; Terry T. Isson; He Zhang; et al. (Earth and Planetary Science Letters, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Complete genome sequence of Paris polyphylla chlorotic mottle virus infecting Paris polyphylla var. yunnanensis in southwest China - Qiongji He; Binghua Chen; Hongying Zheng; Yuhao Cao; Mengyin Hua; Yueyan Yin; Jiejun Peng; Junmin Li; Jianping Chen; Fei Yan; Xuemei Song; Lin Lin (Archives of Virology, 2023)

Joint full waveform inversion of multiple instantaneous attributes - Kai Zhang; Yi-peng Xu; Fei Xie; Cheng-hong Zhu; Zhen-chun Li; Zi-Lin He (Applied Geophysics, 2023)

Asymmetric response of aboveground and belowground temporal stability to nitrogen and phosphorus addition in a Tibetan alpine grassland - Yonghui Wang; Chao Wang; Fei Ren; Xin Jing; Wenhong Ma; Jin‐Sheng He; Lin Jiang (Global Change Biology, 2023)
Anthropogenic eutrophication is known to impair the stability of aboveground net primary productivity (ANPP), but its effects on the stability of belowground (BNPP) and total (TNPP) net primary productivity remain poorly understood. Based on a nitrogen and phosphorus addition experiment in a Tibetan alpine grassland, we show that nitrogen addition had little impact on the temporal stability of ANPP, BNPP, and TNPP, whereas phosphorus addition reduced the temporal stability of BNPP and TNPP, but not ANPP. Significant interactive effects of nitrogen and phosphorus addition were observed on the stability of ANPP because of the opposite phosphorus effects under ambient and enriched nitrogen conditions. We found that the stability of TNPP was primarily driven by that of BNPP rather than that of ANPP. The responses of BNPP stability cannot be predicted by those of ANPP stability, as the variations in responses of ANPP and BNPP to enriched nutrient, with ANPP increased while BNPP remained unaffected, resulted in asymmetric responses in their stability. The dynamics of grasses, the most abundant plant functional group, instead of community species diversity, largely contributed to the ANPP stability. Under the enriched nutrient condition, the synchronization of grasses reduced the grass stability, while the latter had a significant but weak negative impact on the BNPP stability. These findings challenge the prevalent view that species diversity regulates the responses of ecosystem stability to nutrient enrichment. Our findings also suggest that the ecological consequences of nutrient enrichment on ecosystem stability cannot be accurately predicted from the responses of aboveground components and highlight the need for a better understanding of the belowground ecosystem dynamics.

Flexible electrode-based voltammetric detection of Y (III) ions in real water samples using an efficient CyDTA complexing strategy - Yao Liu; Qiang Xue; Zeyu Liu; Lin He; Fei Liu; Haijiao Xie (Journal of Hazardous Materials, 2023)

Effects of submergence stress on germination and seedling growth of direct-seeded rice and evaluation of submergence tolerance - Rongping Zhang; Ningning Zhou; Lin Zhou; Rigui Ashi; Tingyu Feng; Keyuan Zhang; Xuehuan Liao; Lise Aer; Xia Wu; Kangning Yu; Jianchao Shu; Xuewu He; et al. (Paddy and Water Environment, 2023)

Associations of metal mixtures with thyroid function and potential interactions with iodine status: results from a cross-sectional study in MEWHC - Xiaoting Ge; Junxiu He; Sencai Lin; Yu Bao; Yuan Zheng; Hong Cheng; Haiqing Cai; Xiuming Feng; Wenjun Yang; Sihan Hu; Lin Wang; Qijing Liao; et al. (Environmental Science and Pollution Research, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Boosting diethylamine selective oxidation over CuO/ZSM-5 catalyst by CeO2 modification - Lin-Cong He; Hua-Hui Xu; Xing-Yue Leng; Ling-Yun Jin; Ai-Ping Jia; Meng-Fei Luo; Jian Chen (Fuel, 2023)

Fe/Ni layered double hydroxide biocatalysts inhibit tumor growth through ROS and ferroptosis signaling pathway - Qiwen Pan; Fei Lin; Ruiqi Liu; Yilin Li; Xinyue Zhang; Rui Luo; Lingling Cai; Yang Liu; Wuguo Deng; Liru He (Chemical Engineering Journal, 2023)

Legacy effect of plant chemical defence substances on litter decomposition - Yunchao Luo; Lin Wang; Tingting Cao; Weihua He; Shangxian Lu; Fei Li; Zhenwei Zhang; Tong Chang; Xingjun Tian (Plant and Soil, 2023)

Carbon quantum dot fluorescent probe for labeling and imaging of stellate cell on liver frozen section below freezing point - Yan-Fei He; Kai Cheng; Zi-Tao Zhong; Xiao-Lin Hou; Chang-Zhi An; Jing Zhang; Wei Chen; Bo Liu; Jing Yuan; Yuan-Di Zhao (Analytica Chimica Acta, 2023)

Activation of peroxymonosulfate by base for degradation of methylene blue: role of bromide ions - Fei Yang; Yufeng Zhao; Lin He; Zhen Wang (Environmental Science and Pollution Research, 2023)

Palladium-catalyzed Sonogashira coupling to synthesis of gem‑difluoroenynes - Lin Li; Yan Mei; Junlei Zhang; Kehan He; Fei Pan (Journal of Fluorine Chemistry, 2023)

Evolution characteristic of atmospheric black carbon particles at a coastal site in the Pearl River Delta, China - Jing Wei; Xiao-Feng Huang; Yan Peng; Xiao-Yu Lin; Zhen-Hua Lei; Li-Ming Cao; Wen-Fei Zhu; Song Guo; Ling-Yan He (Environmental Pollution, 2023)

Evaluating the performance of a novel ventilated embankment structure in warm permafrost regions by numerical simulation - Zhanyuan Zhu; Zonghang He; Fei Luo; Bin Luo; Chenxuan Tang; Zuyin Zou; Zihong Guo; Weimin Xiao; Xiangang Jiang; Lin Li (Cold Regions Science and Technology, 2023)

Recent progress on highly efficient removal of heavy metals by layered double hydroxides - Tong He; Qian Li; Tong Lin; Jiaxin Li; Sha Bai; Sai An; Xianggui Kong; Yu-Fei Song (Chemical Engineering Journal, 2023)

Environmentally-friendly biorecovery of manganese from electrolytic manganese residue using a novel Penicillium oxalicum strain Z6-5-1: Kinetics and mechanism - Shuai Zhao; Bo-Wen Zheng; Yu-Cang Wang; Fei He; Li-Juan Wang; Xiong Lin; Xue-Mei Luo; Jia-Xun Feng (Journal of Hazardous Materials, 2023)

MiR-29a-3p inhibits high-grade transformation and epithelial–mesenchymal transition of lacrimal gland adenoid cystic carcinoma by targeting Quaking - Fei Xu; Meixia Jiang; Qin Tang; Jiaqi Lin; Xun Liu; Chuanli Zhang; Jinzhi Zhao; Yanjin He; Lijie Dong; Limin Zhu; Tingting Lin (Molecular Biology Reports, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Magnetic nanopromoter enables excellent kinetic promotion and cycling performance in methane hydrate formation - Chen Chen; Haoyu Yuan; Xiaoming Wang; Na Wang; Yan Lin; Yan He; Fei Wang (Chemical Engineering Journal, 2023)

Complete genome sequence of iris potyvirus B infecting Lilium lancifolium in China - Qi Lin; Dankan Yan; Mengying Hua; Yueyan Yin; Hongying Zheng; Jianping Chen; Fei Yan; Jiejun Peng; Qiongji He; Yuwen Lu (Archives of Virology, 2022)

Organic–inorganic calcium lignosulfonate compounds for soil acidity amelioration - Fei Kang; Qi-lin Lv; Jin Liu; Yun-shan Meng; Zi-he Wang; Xue-qin Ren; Shu-wen Hu (Environmental Science and Pollution Research, 2022)

Wheat genomic study for genetic improvement of traits in China - Jun Xiao; Bao Liu; Yingyin Yao; Zifeng Guo; Haiyan Jia; Lingrang Kong; Aimin Zhang; Wujun Ma; Zhongfu Ni; Shengbao Xu; Fei Lu; Yuannian Jiao; et al. (Science China Life Sciences, 2022)

Distribution of Coomassie Blue Stainable Particles in the Pearl River Estuary, China, Insight Into the Nitrogen Cycling in Estuarine System - Cui-Ci Sun; Wei-Zhong Yue; You-Shao Wang; Wei-Hong He; Yi-Guo Hong; Fu-Lin Sun; Hao Cheng; Mei-Lin Wu; Zhao-Yu Jiang; Fei Jiao; Yu-Tu Wang (Frontiers in Marine Science, 2022)
Distributions of Coomassie Blue stainable particles (CSP), the sources and transports, as well as their implications for nitrogen biogeochemical cycles in the Pearl River estuary (PRE) were investigated during two cruises in August 2016 and January 2017. CSP color concentrations (CSP concentration determined spectrophotometrically) were 73.7–685.3 μg BSA eq L –1 [μg Bovine serum albumin (BSA) equivalent liter –1 ] in August 2016 and 100.6–396.4 μg BSA eq L –1 in January 2017, respectively. CSP concentrations were high in low-salinity waters (<5), and declined from the river to the middle estuary by 80% in the wet season and 55.6% in the dry season, respectively, then increased again in the lower estuary due to high primary production. CSP concentrations were mainly associated with chlorophyll a (Chl a ) concentration except for the turbid mixing zone, suggesting that autochthonous phytoplankton production served as the primary source of CSP in the PRE. The concentrations of nitrogen (N) as CSP in the PRE were comparable to the nitrogen content of particulate hydrolysable amino acids (PHAA). Pictures of CSP taken by microscopy and the correlation between composition of PHAA and the ratio of Chl a /CSP color showed that CSP were relatively degraded due to delivery of old terrestrial protein to river section and extensive microbial degradation during mixing at the upper and middle parts of the estuary, whereas CSP in lower estuary appeared to be more labile due to higher fresh algal production. The contribution of CSP nitrogen (CSP-N) to the particulate nitrogen (PN) pool was 34.98% in summer and 30.8% in winter. The conservative estimate of CSP-N input flux in the Pearl River Delta was about 6 × 10 6 mol N d –1 . These results suggested that CSP was a significant pool of organic nitrogen in the PRE. The study of CSP composition in terms of nitrogen provides new insight into the roles of CSP on nitrogen biogeochemical processes in the turbid and productive estuarine system.

Protein kinase PpCIPK1 modulates plant salt tolerance in Physcomitrella patens - Fei Xiao; Xiaochuan Li; Jiaxian He; Jinfeng Zhao; Guochun Wu; Qianyuan Gong; Huapeng Zhou; Honghui Lin (Plant Molecular Biology, 2021)

Identification of 5S and 45S rDNA sites in Chrysanthemum species by using oligonucleotide fluorescence in situ hybridization (Oligo-FISH) - Jun He; Sisi Lin; Zhongyu Yu; Aiping Song; Zhiyong Guan; Weimin Fang; Sumei Chen; Fei Zhang; Jiafu Jiang; Fadi Chen; Haibin Wang (Molecular Biology Reports, 2021)

Isolation and characterization of two new chroman-4-ones from the endophytic fungus Penicillium chrysogenum obtained from Eucommia ulmoides Oliver - Sheng-Yue Liu; Li-Zhi Wang; Yue-Fei Wang; Lin Li; Guo-Ying Han; Bing-Yang Zhang; Ying Guo; Yong-Zhi He; Shi-Ming Fang; Han Zhang (Natural Product Research, 2020)

Association of in-hospital intensive statins dosage and death in arteriosclerotic cardiovascular disease with percutaneous coronary intervention: insights of multicentre cohort from China - Peng-yuan Chen; Yuan-hui Liu; Chong-yang Duan; Hua-lin Fan; Li-huan Zeng; Wei Guo; Lei Jiang; Xue-biao Wei; Wen-fei He; Sha Tao; Zhi-qiang Guo; Ji-yan Chen; et al. (European Journal of Clinical Pharmacology, 2020)

Immunogenicity noninferiority study of 2 doses and 3 doses of an Escherichia coli-produced HPV bivalent vaccine in girls vs. 3 doses in young women - Yue-Mei Hu; Meng Guo; Chang-Gui Li; Kai Chu; Wen-Gang He; Jing Zhang; Jian-Xiang Gu; Juan Li; Hui Zhao; Xiang-Hong Wu; BiZhen Lin; Zhi-Jie Lin; et al. (Science China Life Sciences, 2020)

Endometrial autophagy is essential for embryo implantation during early pregnancy - Yan Su; Juan-Juan Zhang; Jun-Lin He; Xue-Qing Liu; Xue-Mei Chen; Yu-Bin Ding; Chao Tong; Chuan Peng; Yan-Qing Geng; Ying-Xiong Wang; Ru-Fei Gao (Journal of Molecular Medicine, 2020)

Novel mutations in SPEF2 causing different defects between flagella and cilia bridge: the phenotypic link between MMAF and PCD - Chaofeng Tu; Hongchuan Nie; Lanlan Meng; Weili Wang; Haiyu Li; Shimin Yuan; Dehua Cheng; Wenbin He; Gang Liu; Juan Du; Fei Gong; Guangxiu Lu; et al. (Human Genetics, 2020)

Metabolomic profiling on rat brain of prenatal malnutrition: implicated for oxidative stress and schizophrenia - Fei Xu; Xin Li; Weibo Niu; Gaini Ma; Qianqian Sun; Yan Bi; Zhenming Guo; Decheng Ren; Jiaxin Hu; Fan Yuan; Ruixue Yuan; Lei Shi; et al. (Metabolic Brain Disease, 2019)

Insights into removal of tetracycline by persulfate activation with peanut shell biochar coupled with amorphous Cu-doped FeOOH composite in aqueous solution - Jian Xu; Xueliang Zhang; Cheng Sun; Jinzhong Wan; Huan He; Fei Wang; Yuxuan Dai; Shaogui Yang; Yusuo Lin; Xinhua Zhan (Environmental Science and Pollution Research, 2019)

Spatial patterns in natural Picea crassifolia forests of northwestern China, as basis for close-to-nature forestry - Zhi-bin He; Shu Fang; Long-fei Chen; Jun Du; Xi Zhu; Peng-fei Lin (Journal of Mountain Science, 2018)

Effects of different initial pH and irradiance levels on cyanobacterial colonies from Lake Taihu, China - Fei Fang; Yan Gao; Lin Gan; Xiaoyun He; Liuyan Yang (Journal of Applied Phycology, 2018)

Necroptosis may be a novel mechanism for cardiomyocyte death in acute myocarditis - Fei Zhou; Xuejun Jiang; Lin Teng; Jun Yang; Jiawang Ding; Chao He (Molecular and Cellular Biochemistry, 2018)

Microsatellite records for volume 10, issue 1 - Ai-Qing Yu; Chengxin Fu; Chongbo He; Fei Liu; Guo-Hua Ding; Hongman Hou; Jian Zhao; Jianmin Yang; Jiansheng Wang; Kun-ci Chen; Lan-lan Zhang; Pan Li; et al. (Conservation Genetics Resources, 2018)

Correlation analyses revealed global microRNA–mRNA expression associations in human peripheral blood mononuclear cells - Lan Wang; Jiang Zhu; Fei-Yan Deng; Long-Fei Wu; Xing-Bo Mo; Xiao-Wei Zhu; Wei Xia; Fang-Fei Xie; Pei He; Peng-Fei Bing; Ying-Hua Qiu; Xiang Lin; et al. (Molecular Genetics and Genomics, 2018)

Sensitivity of Colletotrichum acutatum to six fungicides and reduction in incidence and severity of chili anthracnose using pyraclostrobin - Yang-Yang Gao; Li-Fei He; Bei-Xing Li; Wei Mu; Jin Lin; Feng Liu (Australasian Plant Pathology, 2017)

Preparation and Evaluation of Diosgenin Nanocrystals to Improve Oral Bioavailability - Cui-zhe Liu; Jin-hua Chang; Lin Zhang; He-fei Xue; Xi-gang Liu; Pei Liu; Qiang Fu (AAPS PharmSciTech, 2017)

The potential of fludioxonil for anthracnose control on China chili fruit - Yang-Yang Gao; Li-Fei He; Bei-Xing Li; Wei Mu; Jin Lin; Feng Liu (Phytoparasitica, 2017)

Two ultraviolet radiation datasets that cover China - Hui Liu; Bo Hu; Yuesi Wang; Guangren Liu; Liqin Tang; Dongsheng Ji; Yongfei Bai; Weikai Bao; Xin Chen; Yunming Chen; Weixin Ding; Xiaozeng Han; et al. (Advances in Atmospheric Sciences, 2017)

Integrative multi-omics analysis revealed SNP-lncRNA-mRNA (SLM) networks in human peripheral blood mononuclear cells - Wei Xia; Xiao-Wei Zhu; Xin-Bo Mo; Long-Fei Wu; Jian Wu; Yu-Fan Guo; Ke-Qin Zeng; Ming-Jun Wang; Xiang Lin; Ying-Hua Qiu; Lan Wang; Pei He; et al. (Human Genetics, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Branched polymeric prodrug/programmed cell death 4 complexes for combinational cancer therapy - Yu-Jing He; Lei Xing; Peng-Fei Cui; Jia-Liang Zhang; Jian-Bin Qiao; Cheng-Qiong Luo; Ge Jiang; Hu-Lin Jiang (Journal of Pharmaceutical Investigation, 2017)

A novel process for obtaining pinosylvin using combinatorial bioengineering in Escherichia coli - Jing-long Liang; Li-qiong Guo; Jun-fang Lin; Ze-qi He; Fa-ji Cai; Jun-fei Chen (World Journal of Microbiology and Biotechnology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Observed features of temperature, salinity and current in central Chukchi Sea during the summer of 2012 - Yan He; Na Liu; Hongxia Chen; Fei Teng; Lina Lin; Huiwu Wang (Acta Oceanologica Sinica, 2015)

Vimentin Regulates Neuroplasticity in Transected Spinal Cord Rats Associated with micRNA138 - Bao-Jiang Qian; Ling You; Fei-Fei Shang; Jia Liu; Ping Dai; Na Lin; Mu He; Ran Liu; Yuan Zhang; Yang Xu; Yun-Hui Zhang; Ting-Hua Wang (Molecular Neurobiology, 2015)

Bacillus vanillea sp. nov., Isolated from the Cured Vanilla Bean - Yong-gan Chen; Feng-lin Gu; Ji-hua Li; Fei Xu; Shu-zhen He; Yi-ming Fang (Current Microbiology, 2015)

Mapping Quantitative Trait Loci for Omega-3 Fatty Acids in Asian Seabass - Jun Hong Xia; Grace Lin; Xiaoping He; Bu Yunping; Peng Liu; Feng Liu; Fei Sun; Rongjian Tu; Gen Hua Yue (Marine Biotechnology, 2014)

The roles of two transcription factors, ABI4 and CBFA, in ABA and plastid signalling and stress responses - Zhong-Wei Zhang; Ling-Yang Feng; Jian Cheng; He Tang; Fei Xu; Feng Zhu; Zhong-Yi Zhao; Ming Yuan; Yang-Er Chen; Jian-Hui Wang; Shu Yuan; Hong-Hui Lin (Plant Molecular Biology, 2013)

Expression of SOCSs in human prostate cancer and their association in prognosis - Jian-guo Zhu; Qi-shan Dai; Zhao-dong Han; Hui-chan He; Ru-jun Mo; Guo Chen; Yan-fei Chen; Yong-ding Wu; Sheng-bang Yang; Fu-neng Jiang; Wei-hong Chen; Zhao-lin Sun; et al. (Molecular and Cellular Biochemistry, 2013)

Down-regulation of the ErbB3 binding protein 1 in human bladder cancer promotes tumor progression and cell proliferation - Hui-chan He; Xiao-hui Ling; Jian-guo Zhu; Xin Fu; Zhao-dong Han; Yu-xian Liang; Ye-han Deng; Zhuo-yuan Lin; Guo Chen; Yan-fei Chen; Ru-jun Mo; Wei-de Zhong (Molecular Biology Reports, 2013)

Iron Overload Inhibits Osteoblast Biological Activity Through Oxidative Stress - Yin-Feng He; Yong Ma; Chao Gao; Guo-yang Zhao; Lin-Lin Zhang; Guang-Fei Li; Yun-Zhi Pan; Kai Li; You-Jia Xu (Biological Trace Element Research, 2013)

WHAMM is required for meiotic spindle migration and asymmetric cytokinesis in mouse oocytes - Xin Huang; Lu Ding; Rui Pan; Peng-Fei Ma; Pan-Pan Cheng; Chun-Hui Zhang; Yu-Ting Shen; Lin Xu; Yu Liu; Xiao-Qin He; Zhong-Quan Qi; Hai-Long Wang (Histochemistry and Cell Biology, 2013)

The isolation of Pi1, an allele at the Pik locus which confers broad spectrum resistance to rice blast - Lixia Hua; Jianzhong Wu; Caixia Chen; Weihuai Wu; Xiuying He; Fei Lin; Li Wang; Ikuo Ashikawa; Takashi Matsumoto; Ling Wang; Qinghua Pan (Theoretical and Applied Genetics, 2012)

Intron retention and 3′-UTR analysis of Arabidopsis Dicer-like 2 transcripts - Qiongji He; Jiejun Peng; Fei Yan; Lin Lin; Yuwen Lu; Hongying Zheng; Hairu Chen; Jianping Chen (Molecular Biology Reports, 2012)

Identification of the novel recessive gene pi55(t) conferring resistance to Magnaporthe oryzae - XiuYing He; XinQiong Liu; Li Wang; Ling Wang; Fei Lin; YongSheng Cheng; ZhaoMing Chen; YaoPing Liao; QingHua Pan (Science China Life Sciences, 2012)

Cloning, characterization, expression, and copper sensitivity of the metallothionein-1 gene in the Chinese mitten crab, Eriocheir sinensis - Fei Ren; Hui Jiang; Jiangling Sun; Lin He; Weiwei Li; Ying Wang; Qun Wang (Molecular Biology Reports, 2011)

Overexpression of PPARγ can down-regulate Skp2 expression in MDA-MB-231 breast tumor cells - Jie Meng; Yun Ding; Aiguo Shen; Meijuan Yan; Fei He; Huoyan Ji; Lin Zou; Yonghua Liu; You Wang; Xiaowei Lu; Huimin Wang (Molecular and Cellular Biochemistry, 2010)

Establishment of cell lines using a doxycycline-inducible gene expression system to regulate expression of hepatitis B virus X protein - Hong Tang; Li Liu; Feng-Jun Liu; En-Qiang Chen; Seishi Murakami; Yong Lin; Fang He; Tao-You Zhou; Fei-Jun Huang (Archives of Virology, 2009)